Risk of acquiring Ascaris lumbricoides infection in an endemically infected rural community in Venezuela. (29th July 2022) - Incani, Renzo Nino; Mughini-Gras, Lapo; Homan, Tobias; Sequera, Ivan; Sequera, Luis; Serrano, Ruth; Sequera, Carlos; Salas, Luis; Salazar, Marisabel; Santos, Paola
Abstract: Soil-transmitted helminths, such as Ascaris lumbricoides, are the most prevalent parasites globally. Optimal anthelmintic treatment for A. lumbricoides in endemically infected communities is challenged by several host-related and environmental factors influencing infection acquisition. We assessed the risk of A. lumbricoides (re)infection after treatment in a Venezuelan rural community. Individual merthiolate-iodine-formaldehyde-fixed faecal samples were collected from 224 persons before a single-dose pyrantel treatment and at 1, 3, 6, 9 and 15 months after treatment. Effects of age, sex and socioeconomic status (SES) on A. lumbricoides prevalence, eggs/gram faeces (EPG) and infection (re)acquisition were assessed using both generalised linear mixed-effects models and survival analysis. Pre-treatment A. lumbricoides prevalence was 39.7%. Higher prevalence was associated with younger age and lower SES. Higher EPG values were observed among young children. Median time to A. lumbricoides infection was six months after treatment: at 1, 3, 6, 9 and 15 months post-treatment, cumulative incidence was 6.7%, 18.9%, 34.6%, 42.2%, and 52.6%, respectively. Younger age, lower SES, and pre-treatment A. lumbricoides infection status showed significantly elevated hazard ratios. Mass drug administration protocols would benefit from considering these factors in selective treatment strategies and possibly more than just annual or biannual treatments in the target population.